Bacterial Profile of Fresh and Spoiled Fish Mince from johnius clussumieri at Refrigerated Storage - T., Jawahar Abraham; G., Sukumar; D., Sukumar; P., Jeyachandran (Fishery Technology, 2025)
Fish mince from Johnius dussumieri was examined for the changes in the bacteriological profile in fresh and spoiled condition at refrigerated storage (4Â±1Â°C). The percentage composition of bacterial flora was found to vary with fresh fish, fresh mince and spoiled mince. Acinetobacter and Aeromonas which were dominant in fresh fish decreased drastically upon mincing, washing and storage. ln fresh mince 71.0% of the bacterial population comprised of gram positive group of which Micrococcus was the dominant. Flora of the spoiled mince was dominated by gram negative group (80.0%) comprising mainly of Vibrio followed by Pseudomonas.